2010
DOI: 10.1007/s12630-010-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

Le vidéolaryngoscope permet une intubation avec un tube à double lumière plus rapide que le laryngoscope standard

Abstract: Purpose This study was designed to compare videolaryngoscopy with direct laryngoscopy with respect to ease of intubation when inserting a double lumen tube (DLT). Methods In this prospective randomized study 68 patients American Society of Anesthesiologists (ASA) physical status I and II were included. Patients with criteria indicating possible difficult intubation were excluded. The patients were randomized into two groups, depending on the tool used to facilitate intubation: videolaryngoscope (VL group) or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
(15 reference statements)
5
8
0
Order By: Relevance
“…In regard to the incidence of dental trauma, a study by comparing DL and VL showed that less force is exerted on the teeth of the upper jaw when using VL (23,24). This is in accordance with the results of the current study situation (6,17). Our dental follow up showed no significant differences in DLT intubation-related injuries.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In regard to the incidence of dental trauma, a study by comparing DL and VL showed that less force is exerted on the teeth of the upper jaw when using VL (23,24). This is in accordance with the results of the current study situation (6,17). Our dental follow up showed no significant differences in DLT intubation-related injuries.…”
Section: Discussionsupporting
confidence: 90%
“…In (8). Considering only the four studies using GlideScope® videolaryngoscopy of that meta-analysis, our results are consistent with three of these four studies (6,7,16,17). Only Hsu et al were able to show shorter intubation times with Glidescope videolaryngoscopy for DLT intubation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Eight studies reported on hypoxia, 23 27-29 50 55 71 79 and only three of these had event data. [27][28][29] Analysis showed no difference in hypoxia according to type of device (OR, randomeffects 0.39, 95% CI 0.10 to 1.44; I 2 ¼70%; n¼1319) (Supplementary Appendix S3).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…38 41 42 78 81 Five studies used both novice and experienced anaesthetists. 28 48 54 68 84 Seven studies did not specify the experience of anaesthetists. 36…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%